Validation of a new test for Schistosoma haematobium based on detection of Dra1 DNA fragments in urine: evaluation through latent class analysis. - Olufunmilola Ibironke; Artemis Koukounari; Samuel Asaolu; Irini Moustaki; Clive Shiff (PLoS Neglected Tropical Diseases)
Background Diagnosis of urogenital schistosomiasis in chronically infected adults is challenging but important, especially because long term infection of the bladder and urinary tract can have dire consequences. We evaluated three tests for viable infection: detection of parasite specific DNA Dra1 fragments, haematuria and presence of parasite eggs for sensitivity (Se) and specificity (Sp). Methods Over 400 urine specimens collected from adult volunteers in an endemic area in Western Nigeria were assessed for haematuria then filtered in the field, the filter papers dried and later examined for eggs and DNA. The results were stratified according to sex and age and subjected to Latent Class analysis. Conclusions Presence of Dra1 in males (Se=100%; Sp=100%) exceeded haematuria (Se=87.6%: Sp=34.7%) and detection of eggs (Se=70.1%; Sp=100%). In females presence of Dra1 was Se=100%: Sp=100%, exceeding haematuria (Se=86.7%: Sp=77.0%) and eggs (Se=70.1%; Sp=100%). Dra1 became undetectable 2 weeks after praziquantel treatment. We conclude detection of Dra1 fragment is a definitive test for the presence of Schistosoma haematobium infection.